Fiddling in biodiversity hotspots while deserts burn? Collapse of the Sahara's megafauna. Issue 1 (28th November 2013) - Durant, S. M.; Wacher, T.; Bashir, S.; Woodroffe, R.; De, P.; Ransom, C.; Newby, J.; Abáigar, T.; Abdelgadir, M.; El Alqamy, H.; Baillie, J.; Beddiaf, M.; et al.
Abstract Biodiversity hotspots understandably attract considerable conservation attention. However, deserts are rarely viewed as conservation priority areas, due to their relatively low productivity, yet these systems are home to unique species, adapted to harsh and highly variable environments. While global attention has been focused on hotspots, the world's largest tropical desert, the Sahara, has suffered a catastrophic decline in megafauna. Of 14 large vertebrates that have historically occurred in the region, four are now extinct in the wild, including the iconic scimitar‐horned oryx (Oryx dammah). The majority has disappeared from more than 90% of their Saharan range, including addax (Addax nasomaculatus), dama gazelle (Nanger dama) and Saharan cheetah (Acinonyx jubatus hecki) – all now on the brink of extinction. Greater conservation support and scientific attention for the region might have helped to avert these catastrophic declines. The Sahara serves as an example of a wider historical neglect of deserts and the human communities who depend on them. The scientific community can make an important contribution to conservation in deserts by establishing baseline information on biodiversity and developing new approaches to sustainable management of desert species and ecosystems. Such approaches must accommodate mobility of both people and wildlife so that they can use resources most efficiently in the face of low and unpredictable rainfall. This is needed to enable governments to deliver on their commitments to halt further degradation of deserts and to improve their status for both biodiversity conservation and human well‐being. Only by so‐doing will deserts be able to support resilient ecosystems and communities that are best able to adapt to climate change.